(Re)Construir movimiento pedagógico en Chile pensando en conjunto el trabajo docente - Zurita, Felipe; Cabaluz, Fabian; Campos Martínez, Javier (Ariadna Ediciones, 2022)
The teaching work has been questioned by the demands for justice and dignity raised throughout the plurinational territory; who in the midst of exhausting work days, where the pressure for the results in standardized tests, the de-professionalization and the lack of autonomy are constant subjects of discomfort, overwhelm and precariousness, have assumed positions of denunciation with respect to the violations to the rights human beings, they have had to respond and resist the accusations of the conservative sectors of society that have accused them of wanting to "politicize" or "ideologize" the education of the new generations; The pandemic and the confinement policies have abruptly and overwhelmingly installed remote education (in synchronous and asynchronous formats), the use of platforms and computer supports previously unknown or unrelated to teachers, enormous problems of inequality in access to devices technology and internet connection networks, which has further increased the social gaps between students at different levels of the educational system.